Logo dan Tagline “Siak The Truly Malay” Kabupaten Siak Provinsi Riau dalam Hukum Kepariwisataan - Adi Tiara Putri; Ledy Diana (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2021)
Regional logos and taglines are useful for promoting areas to attract tourists. With the logo and tagline, it can introduce interesting culture and tourism in the area. In general, the logo and tagline of an area will reflect something unique to that area. logos and taglines also become the identity of an area. In general, what is used as a logo or tagline from an area is a characteristic or something that can remind you of an area, such as its special food, its distinctive dances, tourist attractions, regional characteristics, and many others. So with the logo and tagline, people will easily remember an area. Likewise the logo and tagline used by Siak Regency, namely Siak the Truly Malay. The logo and tagline show that tourism in Siak Regency is based on Malay culture because Siak Regency also adheres to the Malay culture and the Malay culture in Siak Regency is very strong. The Siak Regency logo and tagline also introduces the many types of culture that exist in Siak Regency, with this it will attract a lot of tourists to get to know more and learn about the culture and tourism in Siak Regency. The type of research used is juridical normative with a statutory approach and a case approach. The research also examines the legal aspects of the tourism logo and tagline in Siak Regency according to the tourism law. KEYWORDS : Logo and Tagline, Tourism Law, Malay Culture.